DETERMINASI MADRASAH EFEKTIF - Opik Abdurrahman Taufik (Jurnal Administrasi Pendidikan, 2014)
Reformasi pendidikan di kawasan Asia dijelaskan dengan adanya tiga gelombang pergerakan keunggulan pada sekolah-sekolah dengan model school effective dan school improvement. Madrasah adalah salah satu lembaga pendidikan Islam yang penting di Indonesia memerlukan pengelolaan yang sesuai dengan tuntutan perkembangan zaman. Salah satu Madrasah Aliyah unggulan program Kementerian Agama adalah MAN Insan Cendekia Serpong. Tujuan penelitian ini adalah menganalisis keterkaitan kompetensi dan komitmen SDM (Kepala Sekolah, guru dan tenaga kependidikan), monitoring prestasi siswa dalam bidang akademik dan non akademik, partisipasi orang tua, orientasi kebijakan, kepemimpinan kepala madrasah, kurikulum dan evaluasi, budaya madrasah, dan prestasi siswa bidang akademik dan non akademik di MAN Insan Cendekia Serpong. Hasil penelitian ini dapat disimpulkan sebagai berikut: Pertama, Kompetensi Sumber daya manusia madrasah MAN Insan Cendekia Serpong linear dengan kebutuhan sebuah lembaga pendidikan, sehingga berdampak baik pada pelaksanaan program dan kegiatan madrasah. Kedua, Partisipasi Orang tua di MAN Insan Cendekia cukup baik, baik yang diwadahi tingkat kelas (FKOT) sampai tingkat sekolah (Komite Madrasah). Ketiga, Kepemimpinan kepala madrasah menggunakan pendekatan yang kondusif dalam menciptakan suasana peningkatan mutu madrasah. Keempat, Budaya madrasah Insan Cendekia Serpong berbanding lurus dengan pencapaian hasil belajar siswa.Education reform in the region described by the three-wave movements excellence in schools with effective school models and school improvement. Madrasah is one of the important institutions of Islamic education in Indonesia requires management to suit the demands of the times. One of the Madrasah Aliyah is the flagship program of the Ministry of Religious MAN Insan Cendekia Serpong. The purpose of this study was to analyze the relationship of competence and commitment of human resources (The Principal, teachers and education personnel), monitoring student achievement in academic and non-academic, parent participation, policy orientation, principal leadership, curriculum and evaluation, Islamic culture, and achievements students' academic and non-academic fields in MAN Insan Cendekia Serpong. The results of this study can be summarized as follows: First, human resource competencies MAN Insan Islamic Scholar Serpong linearly with the needs of an educational institution, so the impact both on the implementation of the program and activities of madrasas. Second, participation in MAN Insan Cendekia Parents pretty good, both housed on grade level (FKOT) up to the level of school (Madrasah Committee). Third, principal leadership approach in creating an atmosphere conducive madrasah quality improvement. Fourth, MAN Insan Cendekia Serpong proportional to the achievement of student learning outcomes.